«ҚОБЛАН» ДӘСТАНЫНЫҢ ЖАЗЫП АЛЫНЫЎЫ ҲӘМ АТҚАРЫЎШЫЛАРЫ ҲАҚҚЫНДА - Палымбетов, К.С. (FAN va JAMIYAT, 2018)
The article is about written and oral forms of expression and performing of the Karakalpak folk epos ―Koblan‖. On the basis of succession of performing eposes from a tutor to a learner it is analyzed the repertoire of different performers. The peculiarities of different variants of performing the epos have been revealed on the basis of the analysis.